2022
DOI: 10.1155/2022/2870419
|View full text |Cite
|
Sign up to set email alerts
|

Breast Self-Examination Knowledge and its Determinants among Female Students at Addis Ababa University, Ethiopia: An Institution-Based Cross-Sectional Study

Abstract: Introduction. Breast self-examination is a noninvasive, low-cost screening method for breast cancer detection. A thorough awareness of breast self-examination enables the early detection of breast abnormalities and dramatically lowers breast cancer complications and mortality. The purpose of this study was to investigate the level of knowledge about breast self-examination and its associated factors among female students at Addis Ababa University, Ethiopia. Methods. An institution-based cross-sectional study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 34 publications
3
4
2
Order By: Relevance
“…Many studies conducted in regions such as Asia, Turkey, Africa, and the Arab peninsula, applications have achieved similar results to our study findings and have shown a very low knowledge of BSE (average 20%) [8,14,39,[42][43][44]. However, in a study conducted with female university students in Ethiopia, the rate of having good BSE knowledge was found to be 49.9% [45]. These results suggest that BSE is a less well-known practice and requires the broad participation of women to improve this situation.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies conducted in regions such as Asia, Turkey, Africa, and the Arab peninsula, applications have achieved similar results to our study findings and have shown a very low knowledge of BSE (average 20%) [8,14,39,[42][43][44]. However, in a study conducted with female university students in Ethiopia, the rate of having good BSE knowledge was found to be 49.9% [45]. These results suggest that BSE is a less well-known practice and requires the broad participation of women to improve this situation.…”
Section: Discussionsupporting
confidence: 88%
“…The correct age to begin BSE was misidentified by women from all backgrounds, including doctors. The overall percentage was still higher than the study conducted in Ethiopia, where the aggregate was 32% [17].…”
Section: Discussioncontrasting
confidence: 68%
“…The correct age to begin BSE was misidentified by women from all backgrounds, including doctors. The overall percentage was still higher than the study conducted in Ethiopia, where the aggregate was 32% [ 17 ]. There is a need to educate women about the correct age for commencing BSE, including the health care staff, who seemed uncertain about it.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Hence, an older age could be considered more appropriate starting point for BSE. But considering the awareness impetus of BSE and based on recent studies [ 21 , 22 ] age 20 could also be considered as the correct starting age. Another important point to be noted is that the Shanghai study [ 9 ] showed that there is no preferred method of BSE which could bring survival benefits in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%